Subjectivity and conversion in the foucaultian thought of the care of self - Silva Iauany, Samuel Martins [UNESP]; Verissimo, Danilo Saretta [UNESP] (My University, 2018)
In this paper, we discuss issues related to Foucault's theoretical process which lay the groundwork for his later thought. Then, we discuss Foucault's notion of the descriptive category conversion to the self (se convertere ad se), as well as its influence on the ethical-aesthetic prism of subjectivation. We, then, introduce the notion of subject that is present in early Foucauldian ontologies, which, according to Deleuze(1986/2006), refer to the axis of knowledge and the axis of power. Within this theoretical framework, which encompasses man as an effect of subject/object, psychology is one of the main targets of Foucault's investigation and criticism and serves as an example of what modern science has conceived as a generalized idea of Man. Finally, we explore the conceptual web of The hermeneutics of the subject, in which Foucault describes a new dimension of subjectivity: the relation to self. In the 1982 lectures, this dimension stems from a genealogy of Western practices that connect subject and truth and are determined by the precepts epimeleia heatou (Care of the Self) and gnothise auton (Knowledge of the Self). The philosophical lines derived from each of these principles result in a specific idea of subject. Given this scenario, Foucault turns toward the self-subjectivation perspective of the Greco-Roman conversion to the self, which is part of the spectrum where the care of the self prevails.
Subjetividade e conversão no pensamento foucaultiano do cuidado de si1
Keywords: Conversion to the self; Foucault; Subjectivation